PERAN PEMBINA DALAM MENANAMKAN KEMANDIRIAN BAGI ANAK PENYANDANG TUNAGRAHITA DI SLB ARNADYA MAKASSAR - Annisa, Nur; Alang, Sattu; Syamsidar (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2023)
This research raises the main problem of "The Role of Coaches in Instilling Independence for Children with Intellectual Disabilities at SLB Arnadya Makassar", with sub-problems: 1. What form of special guidance is given to children with intellectual disabilities at SLB Arnadya Makassar? 2. What are the results of the efforts made by the coaches in providing special guidance to foster independence for children with intellectual disabilities at SLB Arnadya Makassar. This research uses a type of descriptive qualitative research located at SLB Arnadya, Bangkala Village, Manggala District, Makassar City, using a Guidance approach. The primary data sources for this research are Wahyu Dwi Pranita Purbasary (Guardian of Mentally Disabled Children), Asmirawati (Guardian of Mentally Disabled Children) as key informants and additional informants, namely Hj. Arniwati Alias Sukaena (Principal of Arnadya Makassar Special School), Silvia (Parents of students with intellectual disabilities), Mira (Parents of students with intellectual disabilities), Hasni (Parents of students with intellectual disabilities), Nisa (Children with intellectual disabilities), Aqilah (Children with intellectual disabilities). Secondary data sources are books, theses, journals, literature and other data sources. The methods used in collecting data are observation, interviews and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research show that there are two forms of special guidance provided by coaches in fostering the independence of mentally retarded children at the Arnadya Makassar Special School (SLB), namely: 1. Self-development, by providing motivation to be able to behave creatively and independently, 2. Religious approach, by providing teaching related to religion so that they are able to behave in accordance with norms. And the results of providing special guidance carried out by the coaches at SLB Arnadya, can be seen from: 1. Able to foster a sense of self-confidence in mentally retarded children, 2. Forming high enthusiasm for mentally retarded children, 3. Forming commendable morals in mentally retarded children in Special Schools (SLB) Arnadya Makassar). The implications of this research are: 1. It is hoped that the Head of SLB Arnadya Makassar can add teaching staff in coaching at SLB Arnadya Makassar. 2. The public should increase awareness of the existence of children with special needs, especially children with mental retardation.